Short-Term Side Effects and SARS-CoV-2 Infection after COVID-19 Pfizer–BioNTech Vaccine in Children Aged 5–11 Years: An Italian Real-World Study - Martina Capponi; Federica Pulvirenti; Bianca Laura Cinicola; Giulia Brindisi; Maria Giulia Conti; Giovanni Colaiocco; Giovanna de Castro; Cristiana Alessia Guido; Marzia Duse; Fabio Midulla; Anna Maria Zicari; Alberto Spalice (Vaccines, 2022)
Vaccination against COVID-19 is the most effective tool to protect both the individual and the community from this potentially life-threatening infectious disease. Data from phase-3 trials showed that two doses of the BNT162b2 vaccine were safe, immunogenic, and effective against COVID-19 in children aged 5–11 years. However, no surveys in real-life settings have been carried out in this age range. Here, we conducted a cross-sectional study to evaluate the short-term adverse reactions (ARs) and the rate of protection against infection of the BNT162b2 vaccine in children aged 5–11 years by the compilation of two surveillance questionnaires conceived using Google Forms. Five-hundred and ninety one children were included in the analysis. ARs were reported by 68.9% of the children, being mainly local. The incidence of systemic ARs, especially fever, was higher after the second dose. The incidence of infection after completing the immunization accounted for 13.6% of the children. COVID-19 symptoms reported were mild, with the exception of one case of pneumonia. Only 40% of infected participants needed to take medication to relieve symptoms, mostly paracetamol and NSAIDs, and none reported persistent symptoms. The Pfizer–BioNTech vaccine in children aged 5–11 years is safe and well tolerated. The mild clinical course of COVID-19 in immunized children confirmed the favorable risk–benefit ratio, encouraging parents to immunize their children.